Nature of a white opaque substance visualized by magnifying endoscopy in colorectal hyperplastic polyps - Hirano, Akikazu; Yao, Kenshi; Ishihara, Hiroshi; Hisabe, Takashi; Imamura, Kentaro; Kanemitsu, Takao; Ohtsu, Kensei; Hasegawa, Rino; Ikezono, Go; Takeda, Kazuhiro; Miyaoka, Masaki; Ueki, Toshiharu; Tanabe, Hiroshi; Haraoka, Seiji; Iwashita, Akinori (Endoscopy International Open, 2021)
Background and study aims A white opaque substance (WOS) has been observed in the epithelia of gastric, duodenal, and colorectal epithelial adenomas and carcinomas, using magnifying endoscopy (ME). The WOS has been reported to be derived from a dense accumulation of minute lipid droplets in the epithelium. This study aimed to investigate whether the WOS in colorectal hyperplastic polyps was derived from lipid droplets accumulated in the epithelium, as observed in the case of gastric, duodenal, and colorectal epithelial neoplasms.Patients and methods We analyzed 30 consecutive patients who were positive for the WOS, as visualized in colorectal hyperplastic polyps by ME with narrow-band imaging and 30 consecutive patients who were negative for the WOS. Biopsy specimens obtained from the polyps were immunostained with anti-adipophilin antibody to determine the correlation between the presence of the WOS and that of lipid droplets in the epithelium.Results In all patients, the epithelial cells were histologically positive for adipophilin. However, the area of adipophilin-positive epithelial cells in the WOS-positive group was significantly larger than that in the WOS-negative group (P < 0.001). The density of the WOS was strongly and positively correlated with the area of adipophilin-positive cells.Conclusions This study reveals that the WOS visualized in the superficial layers of colorectal hyperplastic polyps is produced by a dense accumulation of minute lipid droplets in the epithelia of the polyps.